An assessment of the role of the falx cerebri and tentorium cerebelli in the cranium of the cat (Felis silvestris catus). Issue 147 (24th October 2018) - Sellés de Lucas, Víctor; Dutel, Hugo; Evans, Susan E.; Gröning, Flora; Sharp, Alana C.; Watson, Peter J.; Fagan, Michael J.
Abstract : The falx cerebri and the tentorium cerebelli are two projections of the dura mater in the cranial cavity which ossify to varying degrees in some mammalian species. The idea that the ossification of these structures may be necessary to support the loads arising during feeding has been proposed and dismissed in the past, but never tested quantitatively. To address this, a biomechanical model of a domestic cat ( Felis silvestris catus ) skull was created and the material properties of the falx and tentorium were varied for a series of loading regimes incorporating the main masticatory and neck muscles during biting. Under these loading conditions, ossification of the falx cerebri does not have a significant impact on the stress in the cranial bones. In the case of the tentorium, however, a localized increase in stress was observed in the parietal and temporal bones, including the tympanic bulla, when a non-ossified tentorium was modelled. These effects were consistent across the different analyses, irrespective of loading regime. The results suggest that ossification of the tentorium cerebelli may play a minor role during feeding activities by decreasing the stress in the back of the skull.